DELEGATION OF AUTHORITY AND EMPLOYEE PERFORMANCE AFFECT MANAGEMENT DECISION MAKING EFFECTIVENESS IN PT. SOLUSI GUNA SEJAHTERA-BEKASI - Jusdienar, Akka Latifah; Firdaus, Ahmad; Zendrato, Yuniria (STIE Pelita Nusantara Semarang, 2024)
This study explores the relationship between effective Delegation of authority and employee performance, highlighting the importance of clear communication, trust-building, and well-defined responsibilities in managerial decision-making. It examines the role of Delegation as a strategic tool for managers to empower employees and the impact of employee performance on management decision-making. High-performing employees can contribute valuable insights, innovative ideas, and data-based recommendations, while poor performance can lead to errors, misjudgments, and suboptimal choices. The interaction between Delegation and employee performance is analyzed, revealing a symbiotic relationship. Effective Delegation can stimulate employee engagement and motivation, leading to improved performance, while outstanding performance can strengthen managers' confidence in delegations, allowing them to entrust more responsibility to employees. On a scale of 1 to 5, the statements in the questionnaire are rated. SEM (Structural Equal Model) analysis on SmartPLS 4.0 in use the research findings indicate that (1) employee performance positively influences managerial decision-making, and (2) delegation positively influences managerial decision-making.